FOREWORD FROM HANDLING EDITOR - 7TH EDITION - Sodri, Ahyahudin (UI Scholars Hub, 2021)
We are delighted to present the 7th edition of JESSD, published in December 2021. We have selected seven of the best articles from Nigeria, Malaysia, Uganda, Tajikistan, and Japan for this edition that related with topic of Environmental Science and Sustainable Development.